Perancangan Sistem Manajemen Billing untuk Modul Praktikum Jaringan Telepon Seluler Transmisi WiFi 2,4 Ghz - Anky Ismas Sasongko (Jurnal Jaringan Telekomunikasi, 2018)
This study aims to design and build a VoIP billing server that is used for calculating the cost of telephone conversations and designing a VoIP practicum module for students.The research method was carried out by conducting literature studies, network design planning, device configuration, determination of billing parameters and VoIP call testing to determine call quality and VoIP billing function.The result of this thesis is a telephone billing system application that is used to calculate VoIP-based telephone costs and the softphone application as a telecommunications medium. Where the billing server is well configured with the softphone application, the softphone application uses the simcard as data verification provided by the admin. The results of testing the success of telephone charges when 2 clients make calls with an initial pulse of 100 Rupiah, the result is a calculation of 100% between manual calculations and program calculations. And when the test was carried out, making calls more than 2 clients produced different data between manual and program calculations with an average of 101.75, the program calculation was on manual calculation of 100.The results of this difference were only for the first and second callers, the next caller had the results which is the same as manual calculation.